Systematics and morphology of American mosasaurs - Russell, Dale A. (Peabody Museum of Natural History, Yale University, 2020)
A classic work from the Yale Peabody Museum of Natural History describing the mosasaurs, a group of large predatory marine lizards of the Mesozoic.